Splenogonadal Fusion: Pathogenesis, Diagnosis and Management - Khouloud Ben Lazreg; Imen Helal; Fatma Khanchel; Aida Daieb; Sameh Tlili; Sirine El Fekih; Ehsen Ben Brahim; Youssef Hellal; Raja Jouini; Achraf Chadli Debbiche (Medical Research and Its Applications Vol. 10, 2024)
Splenogonadal fusion is an abnormal connection between the spleen and gonads. This rare entity can be easily confused with testicular tumors. It usually accompanies congenital malformations, such as cryptorchidism, making diagnosis more difficult. Herein, we report two rare cases of this challenging diagnosis. The first case involved a 5-year-old child admitted for management of bilateral testicular cryptorchidism complicated by an inguinal hernia on the left. Intraoperatively, we discover a globular left testis with two red ovoid formations of 4mm. There was no connection between the testis and the lower edge of the spleen. One of these formations was biopsied, showing normal splenic parenchyma and confirming the diagnosis of splenogonadal fusion. The second case was a 9-month-old infant followed for a disorder of sex differentiation, stage III of Prader with a 46, XY genotype. Diagnostic laparoscopy showed bilateral testicular cryptorchidism with intraabdominal testes. There was a left testicular nodule connected to the lower cryptorchidism edge of the spleen with a cord-like structure. A biopsy of the nodule showed normal splenic parenchyma. Bilateral orchidopexy was performed without removal of the left testicular nodule. Our two cases highlight the fact that surgeons must be aware of this entity to avoid unnecessary orchiectomy. In some cases, a biopsy may help with diagnosis.